2009
DOI: 10.1007/s12010-009-8708-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Functionalization of Wool via mTGase-Catalyzed Grafting of ε-Poly-l-lysine

Abstract: epsilon-Poly-L-lysine (epsilon-PL), a natural biomacromolecule having a broad spectrum of antibacterial activity, was grafted on the wool fiber via the acyl transfer reaction catalyzed by microbial transglutaminase (mTGase) to develop a new strategy for antibacterial functionalization of proteinous materials. The effects of the concentrations of epsilon-PLs and mTGases on the graft yields were investigated. A coating of epsilon-PL that almost completely covered the scale profile on the wool surface was visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Furthermore, transglutaminase has been employed to graft casein (Cui et al 2011), gelatin (Cui et al 2009), and silk proteins (Cortez et al 2007) onto wool yarns, generating products with improved physicomechanical properties such as increased tensile strength and higher smoothness. In a similar approach, wool fibers have been functionalized with ε-linked polylysine, an FDA-approved biomolecule with antibacterial properties (Wang et al 2010). Recent studies demonstrated that tyrosinase can be employed to oxidize tyrosyl side chains of keratin, allowing crosslinking of proteins such as collagen and elastin to wool fibers (Jus et al 2009; Lantto et al 2012).…”
Section: Formation Of Protein Networkmentioning
confidence: 99%
“…Furthermore, transglutaminase has been employed to graft casein (Cui et al 2011), gelatin (Cui et al 2009), and silk proteins (Cortez et al 2007) onto wool yarns, generating products with improved physicomechanical properties such as increased tensile strength and higher smoothness. In a similar approach, wool fibers have been functionalized with ε-linked polylysine, an FDA-approved biomolecule with antibacterial properties (Wang et al 2010). Recent studies demonstrated that tyrosinase can be employed to oxidize tyrosyl side chains of keratin, allowing crosslinking of proteins such as collagen and elastin to wool fibers (Jus et al 2009; Lantto et al 2012).…”
Section: Formation Of Protein Networkmentioning
confidence: 99%
“…For example, in recent years, the uses of biotechnology and nanotechnology have gained significant recognition, not only because of the progressive way of altering textile fibers but also have eco-friendly characteristics [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The m-TGase bio-mordant [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ] and nanoclay [ 17 ] are also the best candidates in the textile industry due to their favorable environmentally friendly properties. Furthermore, the lower toxicity of natural dyes as compared to the synthetic ones was clearly confirmed [ 1 , 4 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to the shortcomings of chemical and irradiation methods, enzymatic graft modification with some biotechnological catalysts such as tyrosinase and microbial transglutaminase has emerged because of their ecofriendly nature and mild application conditions. Laccases (EC 1.10.3.2, p ‐diphenol : dioxygen oxidoreductase) are multicopper glycoproteins that catalyze the monoelectronic oxidation of phenols and aromatic or aliphatic amines to produce reactive radicals in a redox reaction in which molecular oxygen is simultaneously reduced to water .…”
Section: Introductionmentioning
confidence: 99%